Ultrastructural features of collagen in thyroid carcinoma tissue observed by polarization second harmonic generation microscopy - Tokarz, Danielle (Biomed Opt Express, 2015)
Changes in collagen ultrastructure between malignant and normal human thyroid tissue were investigated ex vivo using polarization second harmonic generation (SHG) microscopy. The second-order nonlinear optical susceptibility tensor component ratio and the degree of linear polarization (DOLP) of the SHG signal were measured. The ratio values are related to the collagen ultrastructure, while DOLP indicates the relative amount of coherent signal and incoherent scattering of SHG. Increase in ratio values and decrease in DOLP were observed for tumor tissue compared to normal thyroid, indicating higher ultrastructural disorder in tumor collagen.